Manufacture and design of composite grids - Tsai, Stephen W.; Liu, Kevin K. S.; Manne, Philippe M. (Materiales de Construcción, 1997)
Grid structures have been in use for decades. Many were made of reinforced concrete or metals. Grids made of composite materials offer high stiffness and strength at low mass that are competitive with traditional composite laminates. Commonly available manufacturing processes such as filament winding, pultrusion and tubes made from female molds are used to produce composite grids. Cost effective grids can then be made in large sizes and quantities. Grids derive their global stiffness and strength from their ribs. They are fundamentally different from laminates which derive theirs from plies. The models for stiffness and failure modes can be viewed as simple extensions of laminated plate theory. It is hoped that grids will emerge as one of the common structural forms along with solid, stiffened and sandwich panels. Potential applications of composite grids are also mentioned.